What determines future smoking intentions of 12- to 13-year-old UK African-Caribbean, Indian, Pakistani and white young people? - Markham, W; Aveyard, P; Thomas, H; Charlton, A; Lopez, M; De Vries, H (2004)
It is important to know when designing adolescent smoking interventions how ethnicity and gender influence intention. This paper reports an investigation into how ethnicity influences the smoking intentions of disadvantaged UK African-Caribbean (n = 275), Indian (n = 397), Pakistani (n = 687) and white (n = 1792) 12-13 year olds. The Attitudes-Social influences-Efficacy (ASE) model underpinned the study. It states that ASE determinants (advantages, disadvantages, social acceptance, social norms, modelling, perceived pressure and self-efficacy) directly influence behavioural intention. External factors (country, ethnicity and gender) indirectly influence intention by influencing ASE determinants. ASE determinant scores and future smoking intentions were measured. Linear regression analyses showed that smoking intention varied by ethnicity and gender. Differences in ASE scores largely explained these variations. Ethnicity and gender did not modify the predictive effects of equivalent ASE determinant scores on intention. Being a white boy had a small independent direct influence on intention, which was ascribed to affective beliefs underpinning fitness and sporting prowess. Otherwise, ethnicity had no independent direct effects on intention. Culturally appropriate interventions that aim to change cognitions underpinning ASE determinants and, thus, ASE scores would, consequently, be expected to be equally effective amongst disadvantaged UK African-Caribbean, Indian, Pakistani and white adolescents.